Source of Finance Resorted to, Cost Involved in Financing and Financing Decisions Taken by MSMEs: An Insight into Sports Goods Industry of Punjab. Issue 2 (June 2019) - Mahajan, Divya; Sidhu, Amarjit
The research paper presents research done on access to finance by micro-, small- and medium-sized enterprises (MSMEs). There is a substantial evidence that small firms face larger growth constraints and have less access to formal sources of external finance. The study offers an insight into the sources of finance used by the enterprises of Sports Goods Industry of Punjab. In this article, the relationship or association between age of the MSMEs is studied with source of finance chosen by them, that is, whether there is any pattern witnessed in choosing the source of finance by young and old organisations. The findings were based on interviews conducted with 107 organisations.